1986
DOI: 10.1007/bf01309876
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide analysis with monoclonal antibodies of A type inclusion bodies induced by cowpox virus

Abstract: The antigen in A type inclusion bodies (ATIB) induced by cowpox virus (CPV) was examined by immunofluorescent staining with monoclonal antibodies and polypeptide analysis. In the immunofluorescence (IF) test, these monoclonal antibodies reacted only with cytoplasmic inclusion bodies in cells infected with CPV. The fluorescence became detectable in the cells 6-9 hours after infection with CPV. No fluorescence was detectable in cells infected with CPV in the presence of cytosine-I-beta-D-arabinofuranosyl-HCl (Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…First of all, we found that the 63-kDa protein appears to be essential for virus replication whereas the cowpox virus and VACV proteins are nonessential proteins. Moreover, the 63-kDa protein is a component of IMV, CEV, and EEV particles whereas the cowpox virus ATI protein was not found in purified virions (20,29). The truncated IHD-J VACV ATI protein has been shown to be present on the surface of IMV particles only and to be a specific marker of a fraction of IMVs that are destined to be included in the ATIs (48).…”
Section: Mab Isolationmentioning
confidence: 99%
“…First of all, we found that the 63-kDa protein appears to be essential for virus replication whereas the cowpox virus and VACV proteins are nonessential proteins. Moreover, the 63-kDa protein is a component of IMV, CEV, and EEV particles whereas the cowpox virus ATI protein was not found in purified virions (20,29). The truncated IHD-J VACV ATI protein has been shown to be present on the surface of IMV particles only and to be a specific marker of a fraction of IMVs that are destined to be included in the ATIs (48).…”
Section: Mab Isolationmentioning
confidence: 99%
“…Several major antigens have been shown to be induced in cells infected with CPV and VV, i.e., the nucleoprotein (NP) antigen (24,29), neutralization (NT)-associated antigen (21) and A-type inclusions (ATI) (7)(8)(9). We have identified the polypeptides of the major antigens by immunoprecipitation (IP) with polyclonal antibodies (5,6) and identified those antigens by IP and immunoblotting (western blotting, WB) with a monoclonal antibody (MAb) (11)(12)(13). The NP is a so-called common antigen that shows cross-reactivity with cells infected with either an Orthopoxvirus such as CPV, EV and VV, or a Leporipoxvirus such as the Shope fibroma virus (SFV).…”
mentioning
confidence: 99%
“…The dense solid ATI and the 80K polypeptide reacting with A212 are common to all the CPV and EV strains, while the surface-oriented ATI (shown in Fig. 3g; At antibody described previously by Kitamoto et al, 1986a) and the 160K polypeptide reacting with other antibodies (Kitamoto et al, 1986b) vary from strain to strain. Therefore, the former may represent a common ATI in Orthopoxvirus, whereas the latter may be virus-or strain-specific.…”
mentioning
confidence: 99%
“…The conditions for SDS-PAGE and fluorography were as described previously (Ikuta et al, 1978). The techniques for immunoblotting (Western blotting) with monoclonal antibodies by the method of Towbin et al (1979) with slight modifications have been described in detail elsewhere (Kitamoto et al, 1986a). Mock-infected and infected (24 h after infection, m.o.i.…”
mentioning
confidence: 99%
See 1 more Smart Citation